Label-free colorimetric apta-assay for detection of Escherichia coli based on gold nanoparticles with peroxidase-like amplification. Issue 13 (15th March 2023) - Liu, Mengyue; Zhang, Fengjuan; Dou, Shouyi; Sun, Jiashuai; Vriesekoop, Frank; Li, Falan; Guo, Yemin; Sun, Xia
Abstract : Schematic diagram of label-free colorimetric apta-assay based on AuNPs with peroxidase-like amplification. Abstract : In this work, aptamers against E. coli with better performance were obtained via cell systematic evolution of ligands by exponential enrichment (cell-SELEX) and dissociation constants (Kd) of aptamers were estimated to range from 133.87 to 199.44 nM. Furthermore, the selected aptamer was employed for label-free colorimetric detection of E. coli using gold nanoparticles (AuNPs) with peroxidase-like activity to catalyze the oxidation of tetramethylbenzidine (TMB) by hydrogen peroxide (H2 O2 ) to produce color development. This colorimetric apta-assay started with an aptamer–bacteria binding step, and the concentration of residual aptamers after binding depended on the amount of target bacteria. Then, the amount of separated residual aptamers determined the degree of cetyltrimethylammonium bromide (CTAB)-inhibited catalytic activity of AuNPs, which resulted in a color change from dark blue to light blue. Owing to the excellent peroxidase activity of AuNPs, they could emit strong visible color intensity in less than 1 minute to improve visual detection sensitivity. Under optimized conditions, the sensitivity of detection was 5 × 10 3 CFU mL −1 visually and 75 CFU mL −1 using the UV-vis spectrum with a linear range from 5 × 10 2 to 1 × 10 6 CFU mL −1 . And it had shown a good recovery rate in real samples of water, juice and milk compared with classical counting methods.